CDCP1 (CUB domain containing protein 1) is a potential urine-based biomarker in the diagnosis of low-grade urothelial carcinoma. - Chien-Liang Liu; Hung-Wen Tsai; Shu-Ling Peng; Ching-Ping Chang; Yu-Hao Chang; Huei-Sheng Huang (PLoS ONE, 2023)
Urine-based cytology is non-invasive and widely used for clinical diagnosis of urothelial carcinoma (UC), but its sensitivity is less than 40% for low-grade UC detection. As such, there is a need for new diagnostic and prognostic biomarkers of UC. CUB domain containing protein 1 (CDCP1) is a type I transmembrane glycoprotein highly expressed in various cancers. Using tissue array analysis, we demonstrated that CDCP1 expression in UC patients (n = 133), especially in those with low-grade UC, was significantly higher than in 16 normal persons. In addition, CDCP1 expression in urinary UC cells could also be detected by using immunocytochemistry method (n = 11). Furthermore, in 5637-CD cells, overexpression of CDCP1 affected the expression of epithelial mesenchymal transition-related markers and increased matrix metalloproteinase 2 expression and migration ability. Conversely, the knockdown of CDCP1 in T24 cells had the opposite effects. Using specific inhibitors, we demonstrated the involvement of c-Src/PKCδ signaling in the CDCP1-regulated migration of UC. In conclusion, our data suggest that CDCP1 contributes to the malignant progression of UC and may have the potential as a urine-based biomarker for detecting low-grade UC. However, a cohort study needs to be conducted.